Community-Based Pedestrian and Bicycle Safety Program: Developmental Framework and Process Evaluation. Issue 1 (January 2015) - Sandt, Laura; Marshall, Stephen W.; Ennett, Susan T.
Limited research exists on the process, partners, and resources needed to develop and implement programs addressing pedestrian and bicycle safety. Before communities can evaluate program effectiveness, they first need more guidance on what efforts could theoretically lead to fewer crashes, the extent of program delivery needed before changes in behavior or other outcomes can be measured, and how to assess and improve program delivery. The Watch for Me NC (WFM) intervention is a multifaceted, community-based pedestrian and bicycle safety program implemented in North Carolina. This paper describes the WFM intervention development, assesses program delivery through implementation records, and identifies successes and challenges in implementing behavioral interventions to promote pedestrian and bicycle safety. As a process evaluation, this study proceeds and complements research of program effects on intended outcomes (in progress). The nature, duration, and frequency of the delivery of key program components—including outreach, officer training, law enforcement operations, and media engagement—as well as program costs and partnerships are detailed. Funding, intra-agency partnerships, and data to support decision making were instrumental in WFM implementation. Key program delivery challenges included limited resources (including law enforcement time) to effectively saturate a large, dispersed population and loss of program novelty over time. These results and lessons can help guide researchers and decision makers in developing and evaluating similar programs. These results also suggest process measures that can be used to increase the consistency and comparability of program delivery.